ChemInform Abstract: Catalytic Cyclization Reactions of Huisgen Zwitterion with α‐Ketoesters by in situ Chemoselective Phosphine Oxide Reduction. Issue 31 (August 2015) - Fourmy, Kevin; Voituriez, Arnaud
Abstract The first examples of catalytic cyclization reactions of the Huisgen zwitterion with α‐ketoesters are described.